Determinants of Regency/City Typology Based on HDI Indicators: Case from West Java, Indonesia - Nenny Hendajany; Deden Rizal Riyadi (P4W LPPM IPB, 2022)
West Java is the most populated province in Indonesia, housing 18% of the total population, and its Gini Ratio shows the prevalence of income inequality. Previous studies have shown a relationship between education and income inequality, partly derived from inequality in education. This study explores the condition of education in regencies/cities in West Java by mapping based on agriculture/non-agriculture classifications, length of the school and life expectancy in 4 quadrants. Significant factors that determine a region in a particular quadrant are explored. Quadrant I is a region of non-agricultural basis, and the average education has graduated junior high. Quadrant III is also a non-agricultural base characterized by elementary school graduates. Quadrant IV is an agricultural base with graduates from elementary school. There is no region in quadrant II, a rural base with junior high graduates. With secondary data from 2017, multinomial logit regression was used for analysis. The result showed life expectancy in quadrants I and III was greater than in IV. Population and gender empowerment index characterize an area in quadrants I and III rather than IV. This is clearer when one looks at the marginal effect where the variable population growth and the development of the gender empowerment index significantly reduce the area's chances of being in quadrant IV. Based on the typology results, we suggest that the government pay more attention to areas in quadrant IV so that educational inequality in West Java can be reduced.